Making Ecoenzyme Products From Fruit And Vegetable Waste in Rt 007 Rw 02 Meruya Selatan - Dian Meliantari; Achmad Tarmizi; Siti Annisa Wahdiniawati (Journal of Education Religion Humanities and Multidiciplinary, 2026)
In this community service, the selected partner is the PKK community RT 007 RW 02 South Meruya Village, Kembangan District, West Jakarta. Which is named the Pomegranate Gardening Class which consists of PKK women who use the narrow land in the RT 007 area to create food independence by planting several types of vegetable crops, raising chickens and cultivating catfish. Because the land is narrow, some vegetables are planted hydroponically using chemical fertilizers commonly called AB Mix as well as chemical pesticides that are ready to be purchased. Of course, this requires additional costs to buy these fertilizers. Growing hydroponically means that the vegetables are not organic because they use chemical fertilizers and chemical pesticides. To produce healthier organic vegetables, the Undira PKM team wants to share knowledge so that Partners can produce healthy organic vegetables by making ecoenzymes as an organic fertilizer to replace AB Mix from residual household organic waste.